Open or Conventional Access: Integrity in the Process. (July 2019) - Clarke, Pamela N.
A wave of new publishing options has opened for nursing. This dialogue examines factors, such as quality and cost, that may influence new authors. There are numerous options for young scientists with many new journal titles and promises of a quick review and guaranteed publication. Choices between Open Access and conventional journals can be difficult since higher cost to the author does not correlate with higher quality.